Systematical design of a refrigerator foot height adjustment device - (:unkn) unknown (My University, 2012)
Systematic design is an effective methodology which generates possible designs and eliminates them in a step by step manner. The methodology allows designers to generate sub modules and creates relationships or network between these modules to form to functional structure of the design. Due to its capability of reducing development time and that of satisfying customer requirements it has wide application areas. Height adjustment mechanisms for consumer goods industry are special interest for designers and have limited application area due to fact that such kind of mechanisms cannot totally meet customer requirements and they may be too complex to manage. So, different techniques or approaches must be employed to design a specific mechanism for height adjustment. Systematic design approach is employed in this study to produce potential design proposals together with their driving mechanisms for height adjustable refrigerator foot. First stage of systematic approach employed in this study is definition of the height adjustment problem and design requirements. A wide patent research is then completed to seek for existing solutions. Subsystems and functional structure of height adjustment problem arc then formed using "Technical Process Flow" and "Functional Structure Chart". "Morphological Matrix" is created to illustrate each process step and types of design proposals. Last stage is to evaluate the generated design proposals according to the systematic design philosophy to create a novel conceptual design to be patented. Finally, the novel design produced has been manufactured with rapid prototyping technology for further evaluations. © (2012) Trans Tech Publications.
Keywords: Foot; Height adjustment; Refrigerator; Systematic design